Mahaska, Washington County - Berryhill, Blake (Kansas State University, The Chapman Center for Rural Studies, 2012)
The author uses newspaper articles and historic documents to retell the history of the once bustling town of Mahaska. He also connects larger national events to the causes of Mahaska's decline.
Blake Berryhill, “Mahaska, Washington County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/82.
Keywords: Mahaska; Mormon Trail; Washington County; Bonham; Rock Island Railroad; William Newton